2017
DOI: 10.1111/mmi.13835
|View full text |Cite
|
Sign up to set email alerts
|

Novel coordination of lipopolysaccharide modifications in Vibrio cholerae promotes CAMP resistance

Abstract: Summary In the environment and during infection, the human intestinal pathogen Vibrio cholerae must overcome noxious compounds that damage the bacterial outer membrane. The El Tor and classical biotypes of O1 V. cholerae show striking differences in their resistance to membrane disrupting cationic antimicrobial peptides (CAMPs), such as polymyxins. The classical biotype is susceptible to CAMPs, but current pandemic El Tor biotype isolates gain CAMP resistance by altering the net charge of their cell surface th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…Acid‐induced genes included those that encode several predicted outer membrane porins, including the major outer membrane proteins, OmpU and OmpC, as well as the homolog of a phosphoethanolamine transferase, EptA (also known as PmrC, or polymyxin resistance protein C). EptA homologs have previously been shown to modify the structure of the lipid A portion of lipopolysaccharide (LPS) in Gram‐negative bacteria like Salmonella typhimurium and certain strains of Vibrio cholerae (Lee et al , ; Herrera et al , ). We verified the differential transcription of eptA and ompC (VF_1795) at different growth pHs using qRT‐PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid‐induced genes included those that encode several predicted outer membrane porins, including the major outer membrane proteins, OmpU and OmpC, as well as the homolog of a phosphoethanolamine transferase, EptA (also known as PmrC, or polymyxin resistance protein C). EptA homologs have previously been shown to modify the structure of the lipid A portion of lipopolysaccharide (LPS) in Gram‐negative bacteria like Salmonella typhimurium and certain strains of Vibrio cholerae (Lee et al , ; Herrera et al , ). We verified the differential transcription of eptA and ompC (VF_1795) at different growth pHs using qRT‐PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanolamine transferase‐catalyzed lipid A modification is a conserved mechanism for resisting host innate immunity derived cationic antimicrobial peptides (CAPs) among diverse pathogenic and mutualistic microbes, including Vibrio spp. (Beceiro et al , ; Chen and Groisman, ; Cullen et al , ; Herrera et al , ). Moreover, we show that ethanolamine transferase activity increases the infectivity of V. fischeri.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6). Similarly V. cholerae EptA is capable of phosphoethanolamine transfer to glycinylated substrates (34). Thus phosphoethanolamine and glycine transfer does not occur at the level of enzymatic substrate specificity.…”
Section: Glycine Transferase Almg Promotes Polymyxin Resistancementioning
confidence: 99%
“…Our laboratory recently reported that V. cholerae El Tor has maintained a second LPS modification to promote polymyxin resistance through the addition of phosphoethanolamine residues to lipid A phosphate groups (34). The Vibrio EptA homolog is similar to pEtN transferases found in other pathogens, including Neisseria meningitidis, Salmonella enterica, Campylobacter jejuni, and pathogenic E. coli.…”
Section: Glycine Transferase Almg Promotes Polymyxin Resistancementioning
confidence: 99%
See 1 more Smart Citation